Autologous Chondrocyte Implantation (ACI) for Knee Cartilage Defects: A Review of Indications, Technique, and Outcomes. Issue 2 (February 2018) - Krill, Michael; Early, Nicholas; Everhart, Joshua S.; Flanigan, David C.
Abstract : Autologous chondrocyte implantation (ACI) was first developed in the late 1980s for the treatment of articular cartilage defects in the knee. The first generation of ACI utilized a periosteal patch to contain the cultured chondrocyte solution within the defect. Because of issues with periosteal graft hypertrophy, ACI with use of a collagen membrane patch (second-generation ACI) was developed. Finally, the application of chondrocytes within a matrix (third-generation ACI) was created to improve cell delivery, to allow for minimally invasive implantation, to better replicate normal cartilage architecture, and to accelerate patient rehabilitation. As of December 2016, only 1 third-generation ACI product (matrix-induced autologous chondrocyte implantation, or MACI) has been cleared for marketing by the U.S. Food and Drug Administration (FDA) and is available in the United States. ACI (regardless of generation) is effective for the treatment of high-grade tibiofemoral cartilage defects. However, issues with coronal alignment, ligament laxity/instability, and meniscal deficiency must be addressed or the outcomes following ACI will be poor. Because of the extended time that is required for graft maturation, special consideration must be given to return-to-play protocols as athletes can regain strength and neuromuscular coordination well before the graft has sufficiently matured.